Conhecimentos presentes na disciplina de análise nos cursos de licenciatura em Matemática no Brasil - Silva, Luciano Duarte da [UNESP] (2015)
This research aims to understand the types of knowledge present in CPPs and Teaching Plans of the Discipline of Analysis in Mathematics Licentiate Degree Courses in Brazil. Seeking to contemplate this goal, we set the following guiding question: What are the types of knowledge present in CPPs of the Discipline of Analysis in Mathematics Licentiate Degree Courses in Brazil? Assumptions of qualitative research in documentary mode were adopted, and the corpus of research consisting of 80 Teaching plans of the Discipline of Analysis and 136 Courses Pedagogical Projects (CPPs) in Mathematics licentiate Degree courses, where we extract: menus, contents, objectives, among others. We use as theoretical bases of knowledge for teaching proposals in Shulman (1986), and also research that specifically address aspects of the Discipline of Analysis in Mathematics Licentiate Degree Courses. The data were analyzed and based on the content Analysis procedures in perspective elucidated by Bardin (1977), what enabled us to establish three categories of analysis: (i) Specific Content Knowledge of Analysis Discipline; (ii) Pedagogical Content Knowledge of Analysis Discipline; (iii) Curriculum Knowledge of the Content of Analysis Discipline. These three Categories of analysis were interpreted through a triangulation dialogic movement between the survey data, the theoretical framework, as well as our perceptions. Thus, we have conclued that there is a need to: (i) To overcome the dichotomy between Bachelor's and Licentiate's Degree in Mathematics in the training courses for Mathematics teachers in Brazil; (ii) Restructure the Analysis Discipline in the training courses for Mathematics teachers, being based on the interrelationships among: the specific content knowledge, pedagogical content knowledge and curriculum content knowledge; around the set of real numbers as a central focus of that Discipline